The IMPACT OF GAME-BASED TEACHING PRACTICES IN DIFFERENT CURRICULA ON ACADEMIC ACHIEVEMENT - Arcagok, Serdar (International Online Journal of Education and Teaching, 2021)
This study aims to identify the impact of game-based teaching practices available in different curriculum upon academic achievement through meta-analysis. The meta-analysis method aims at grouping similar studies about a subject, theme or study under the heading of certain criteria and combining the quantitative findings for these studies. 412 studies conducted between the years 2000-2020 were examined according to certain criteria and 54 experimental studies that met these criteria were included in the study in order to determine the effect of game-based teaching practices on academic achievement. The data of 54 experimental studies were analyzed through use of Comprehensive Meta Analysis Program (CMA) and Metawin programs. The study results revealed that the game-based teaching practices applied in different curricula positively affect the students’ academic achievement compared to traditional practices. The effect sizes of game-based curricula were identified to significantly differ across education levels, treatment duration, sample sizes and publication types. Keywords: Game, meta-analysis, curriculum